Pengembangan Wisata Yoga Melalui Tren Wisata Babymoon di Ubud, Bali - Ni Wayan Satri Adnyani (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2017)
“Babymoon” is a new kind of popular tourism activity today because it is done not only by common people but also by many celebrities in the world. Babymoon is a tourism activity which is done by expectant mothers and their couples during the pregnancy period. As a well-known tourist destination, Bali will not pass this opportunity to develop tourism in Bali and always offers a new thing to the tourists. One way to attract more tourists to come to Bali is by offering Yoga as a tourist package to the couples who wants to enjoy their babymoon in Bali as Yoga is considered as a good activity to be done by expectant mother. One of favorite place to enjoy yoga for babymoon is Ubud. Ubud has numerousadvantages as yoga tourist destination while enjoying babymoon in Bali